2009
DOI: 10.1039/b902509j
|View full text |Cite
|
Sign up to set email alerts
|

The use of heterogeneous chemistry for the characterization of functional groups at the gas/particle interface of soot and TiO2 nanoparticles

Abstract: Six gases [N(CH(3))(3), NH(2)OH, CF(3)COOH, HCl, NO(2) and O(3)] were selected to probe the surface of seven different types of combustion aerosol samples (amorphous carbon, flame soot) and three types of TiO(2) nanoparticles using heterogeneous, i.e. gas-surface reactions. The gas uptake to saturation of the probes was measured under molecular flow conditions in a Knudsen flow reactor and expressed as a density of surface functional groups on a particular aerosol, namely acidic (carboxylic) and basic (conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 61 publications
3
39
1
Order By: Relevance
“…The value of γ 0 (dark) = 6×10 −6 determined in the present study using BET surface area, lies between the above two values. On the contrary, Setyan et al (2009) have not observed any NO 2 uptake on the TiO 2 surface. Although these authors did not give any estimation of the upper limit of the uptake coefficient, simple calculations show that the value of γ 0 from the present study would lead to an initial drop of NO 2 signal at least by a factor of 1.5 under their experimental conditions.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The value of γ 0 (dark) = 6×10 −6 determined in the present study using BET surface area, lies between the above two values. On the contrary, Setyan et al (2009) have not observed any NO 2 uptake on the TiO 2 surface. Although these authors did not give any estimation of the upper limit of the uptake coefficient, simple calculations show that the value of γ 0 from the present study would lead to an initial drop of NO 2 signal at least by a factor of 1.5 under their experimental conditions.…”
Section: Discussionmentioning
confidence: 74%
“…Although these authors did not give any estimation of the upper limit of the uptake coefficient, simple calculations show that the value of γ 0 from the present study would lead to an initial drop of NO 2 signal at least by a factor of 1.5 under their experimental conditions. The reason for the lower NO 2 uptake to TiO 2 surface in the study of Setyan et al (2009) compared with the present one, could be the mode of preparation of solid samples. Note that in the present work TiO 2 samples were heated under pumping prior to uptake measurements.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Different combinations of functional groups/structures at the interface may give rise to a different degree of hydrophilic or hydrophobic interaction ( [13] Figure 1). Two important concepts related to Question 2.1 concern contact angle and a common theoretical base for the four classical freezing mechanisms (deposition ice nucleation and condensation, immersion and contact freezing) proposed by Pruppacher and Klett [1].…”
Section: Uncovering the Molecular Identity Of Active Sites For Heteromentioning
confidence: 99%
“…Therefore, the chemical reactivity at the interface of carbonaceous NP's were characterized in terms of surface functional groups using chemical titration at molecular flow conditions in a Knudsen reactor, as described by Setyan et al 29 Briefly, a molecular flow of a reactive probing gas is passed through a reactor containing the sample to specifically interact with functional groups on the surface of the particle during its gasresidence time. The temporary decrease of the exiting gas flow is recorded and can be related to the number of reacting sites on the particle.…”
mentioning
confidence: 99%